Learning a way through ethical problems: Swedish nurses' and doctors' experiences from one model of ethics rounds. - Svantesson M; Löfmark R; Thorsén H; Kallenberg K; Ahlström G (Journal of Medical Ethics, 2008)
OBJECTIVE: To evaluate one ethics rounds model by describing nurses' and doctors' experiences of the rounds. METHODS: Philosopher-ethicist-led interprofessional team ethics rounds concerning dialysis patient care problems were applied at three Swedish hospitals. The philosophers were instructed to promote mutual understanding and stimulate ethical reflection, without giving any recommendations or solutions. Interviews with seven doctors and 11 nurses were conducted regarding their experiences from the rounds, which were then analysed using content analysis. Findings: The goal of the rounds was partly fulfilled. Participants described both positive and negative experiences. Good rounds included stimulation to broadened thinking, a sense of connecting, strengthened confidence to act, insight into moral responsibility and emotional relief. Negative experiences were associated with a sense of unconcern and alienation, as well as frustration with the lack of solutions and a sense of resignation that change is not possible. The findings suggest that the ethics rounds above all met the need of a forum for crossing over professional boundaries. The philosophers seemed to play an important role in structuring and stimulating reasoned arguments. The nurses' expectation that solutions to the ethical problems would be sought despite explicit instructions to the contrary was conspicuous. CONCLUSION: When assisting healthcare professionals to learn a way through ethical problems in patient care, a balance should be found between ethical analyses, conflict resolution and problem solving. A model based on the findings is presented.